Analysis of Fintech Payment Gateway and Tax Incentives on the Financial Performance of MSMEs (Case Study On MSMEs in Asia Mega Mas, Medan) - Kristy, Carin; Putri Wahyuni; Nurul Afzan Najis (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine whether Fintech Payment Gateway and Tax Incentives have a significant effect on the Financial Performance of MSMEs in Asia Mega Mas, Medan. This research uses quantitative data methods and the data source is primary data. The population in this study were all MSMEs located in the Asia Megamas Complex area, totaling 92 MSMEs. The sample of this study amounted to 56 MSMEs obtained by purposive sampling technique. Data analysis and testing consists of validity tests, reliability tests, descriptive statistics, classical assumption tests, multiple regression analysis, partial (t test) and simultaneous (F test) hypothesis testing, and determination coefficient tests. The results showed that the Fintech Payment Gateway had a partially significant effect on the Financial Performance of MSMEs with a tcount value of 2.239> ttable 2.005. Tax Incentives have a partially significant effect on the Financial Performance of MSMEs with a tcount value of 10.424> ttable 2.005. Fintech Payment Gateway and Tax Incentives simultaneously have a significant effect on the Financial Performance of MSMEs with an Fcount value of 153.771> Ftable 3.17 with a regression coefficient value of 85.3%.